A study on hot-water production of hotels in Cyprus: Energy and environmental considerations - Michopoulos, Apostolos; Ziogou, Isidoros; Kerimis, M.; Zachariadis, Theodoros (My University, 2017)
Hotel units are responsible for a significant proportion of energy consumption and carbon dioxide emissions in the tourist sector. This paper focuses on the energy and environmental performance of hot-water production systems utilized by high class hotels in Cyprus in order to formulate appropriate carbon emission mitigation strategies. The main systems used are boilers fired by Liquefied Petroleum Gas or Diesel oil, air-source heat pumps and flat plate solar collectors. The results show that the combination of air-source heat pumps with flat plate solar collectors leads to the lowest primary energy consumption. Therefore, improving the sustainability of the tourism sector in Cyprus requires to phase out the usage of boiler systems that are currently in use in almost all four star and five star hotels and promote the use of solar thermal systems in combination with air-source heat pumps. These findings are relevant for island states and other popular tourist destinations sharing similar characteristics with those of Cyprus and provide a framework for national authorities to plan an appropriate energy and environmental upgrade of the hotel stock.
Keywords: Hotel primary energy consumption; Hot-water production; Carbon dioxide (CO2) emissions; Tourism; Cyprus; Primary energy mitigation strategies; Carbon dioxide emissions mitigation strategies